Impact of meteorological conditions on tropospheric ozone and associated with parameterization methods for quantitative assessment and monitoring - Wang, Deying; Wang, Jizhi; Yang, Yuanqin; Jia, Wenxing; Jiang, Xiaofei; Wang, Yaqiang (Frontiers in Environmental Science, 2022)
In recent years, the heavy ozone pollution events around the world have shown a sudden frequently increase, which has aroused widespread concern in the scientific and the public. It is well known that O3 is driven by photochemical reactions triggered by solar radiation (direct and indirect solar radiation), the O3 concentration calculated by chemical mechanism is mostly significantly lower than the actual O3 observation. Based on the study of the effect of meteorological conditions on the "additional increment" of O3 in three representative regions of Beijing, Hangzhou and Guangzhou from 2015 to 2020, an innovation diagnostic theory algorithm that the cross-cutting effects of atmospheric clouds on the chemical pattern of O3 solar radiation is established in this study. On this basis, a parametric evaluation method of O3 is established. The novelty of this study is (1) Comprehensive influence of the meteorological conditions and photochemical reactions mechanisms on the cross-cutting effects of O3 concentration are given. Especially low-level clouds in the troposphere, which have significantly large variable effects on the reflection and refraction of O3 through solar radiation. Theory quantitative algorithm of cloud scattering, cloud height, cloud volume and cloud structure changes, as well as feedback effects caused by water vapor condensation, which closely related to the transformation of O3 precursors are given. (2) Based on this, a parameterization method for quantitative O3 assessment and monitoring, which is a Parameterization for Linking Ozone pollution with Meteorological conditions. (3) Applying the theoretical algorithm and parameterization method of this study, comparing the changes of O3 in 2018 with 2019, an objective quantitative distinction between emission reduction and meteorological impact was made, showing that emission reduction still played a leading role, with a contribution rate of about 27%. This shows that the created quantitative algorithm of atmospheric cloud theory and the innovative parameterization method can provide an objective quantitative basis for O3 pollution decision-making and public emission reduction.